Immunosuppression for adult steroid-dependent or frequently relapsing nephrotic syndrome: A systematic review and meta-analysis. - Zhi Yong Wong; Chiu Yee Teo; Yan Qi Fiona Wong; Ka Ting Ng; Soo Kun Lim (PLoS ONE)
Objective There is limited evidence on which immunosuppressive agents produce the best outcomes for adult patients with steroid-dependent or frequently relapsing nephrotic syndrome (SDNS/FRNS). This review compares the remission rate and adverse effects of various immunosuppressants used. Methods Studies of adult patients with biopsy-proven SDNS/FRNS, administered any immunosuppressive agents and reported complete remission results as one of the clinical outcomes were included. Articles were independently screened by two researchers. ROBINS-I was used for risk of bias assessment. Random-effects model was used for statistical analysis and corresponding 95% confidence intervals (CIs) were calculated. Results 574 patients across 28 studies were included in the analysis. Patients receiving rituximab have a complete remission rate of 89% (95% CI = 83% to 94%; τ2 = 0.0070; I2 = 62%; overall p < 0.01, low certainty) and adverse event rate of 0.26, cyclosporine (CR 40%; 95% CI = 21% to 59%; τ2 = 0.0205; I2 = 55%; overall p = 0.08, low certainty), tacrolimus (CR 84%; 95% CI = 70% to 98%; τ2 = 0.0060; I2 = 33%; overall p = 0.21, moderate certainty), mycophenolate mofetil (CR 82%; 95% CI = 74% to 90%; τ2 < 0.0001; I2 = 15%; overall p = 0.32, moderate certainty) and cyclophosphamide (CR 79%; 95% CI = 69% to 89%; τ2 = 0; I2 = 0%; overall p = 0.52, moderate certainty). Conclusion Among the commonly used immunosuppressive agents, only rituximab has a statistically significant effect in achieving complete remission among patients with SDNS/FRNS and has a relatively good safety profile, but this is limited by low quality of evidence with high degree of heterogeneity causing a lack of statistical power.